Landowners' motivation for adopting perennial energy crops: drivers, barriers and neighbourhood effects. (3rd July 2018) - Konrad, Maria Theresia; Levin, Gregor; Termansen, Mette
Abstract: Uptake of energy crop production is slow, even though the returns are competitive with traditional crops, suggesting the existence of barriers to adoption. Danish farm-level data from 2006 to 2013 are used to identify incentive mechanisms and potential barriers to uptake. The results identify land quality, existing farm activities and local markets as important conditions. The influence of farm size and the decisions of neighbouring farmers suggest more subtle barriers: learning costs, uncertainties about future markets and start-up costs. The study thus points towards some of the underlying barriers for the uptake of energy crops and potential new policy directions.